2011
DOI: 10.1002/nbm.1661
|View full text |Cite
|
Sign up to set email alerts
|

MR‐visible lipids and the tumor microenvironment

Abstract: MR-visible lipids or mobile lipids are defined as lipids that are observable using proton magnetic resonance spectroscopy in cells and in tissues. These MR-visible lipids are composed of triglycerides and cholesterol esters that accumulate in intracellular neutral lipid droplets, where their MR visibility is conferred as a result of the increased molecular motion available in this unique physical environment. This review will discuss factors that lead to the biogenesis of MR-visible lipids in cancer cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
144
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 144 publications
7
144
2
Order By: Relevance
“…Six groups of lipid peaks were identified in the acquired spectra: methine protons at 5.4 ppm and at 5.2 ppm, protons from the methylene glycerol backbone at 4.3 and 4.1 ppm, a small PUFA peak at 2.8 ppm, methylene protons between 2.0 and 2.3 ppm and at 1.6 and 1.3 ppm, and methyl protons at 0.9 ppm. The lipid resonances at 5.4-5.2, at 2.8 and at 2.3-2 ppm exclusively include proton spins that are connected to at least one carbon double bond, -CH¼CH-, ¼CH-CH 2 -CH¼, and -CH 2 -CH¼CH-CH 2 -, respectively, and thus originate from UFAs (25). The other lipid resonances (4.3-4.1, 1.6-1.3, and 0.9) originate from both saturated and unsaturated fatty acids and the glycerol backbone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Six groups of lipid peaks were identified in the acquired spectra: methine protons at 5.4 ppm and at 5.2 ppm, protons from the methylene glycerol backbone at 4.3 and 4.1 ppm, a small PUFA peak at 2.8 ppm, methylene protons between 2.0 and 2.3 ppm and at 1.6 and 1.3 ppm, and methyl protons at 0.9 ppm. The lipid resonances at 5.4-5.2, at 2.8 and at 2.3-2 ppm exclusively include proton spins that are connected to at least one carbon double bond, -CH¼CH-, ¼CH-CH 2 -CH¼, and -CH 2 -CH¼CH-CH 2 -, respectively, and thus originate from UFAs (25). The other lipid resonances (4.3-4.1, 1.6-1.3, and 0.9) originate from both saturated and unsaturated fatty acids and the glycerol backbone.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile lipid composition, detectable by proton MRS, has been associated with cancer and can thus serve as a potential biomarker (25,26). Lipids, among others, consist of fatty acids, which can be divided into fatty acids containing a carbon double bond (C¼C; unsaturated fatty acids [UFAs]) and fatty acids containing no carbon double bonds (saturated fatty acids).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR detection of the mobile lipids in these droplets has been used as a non-invasive method for detecting tumour cell death in vivo [31][32][33]. A recent study suggested that this LD accumulation is due to inhibition of fatty acid oxidation in the mitochondria, as a result of an increase in intra-mitochondrial reactive oxygen species (ROS), which diverts fatty acids away from oxidation and towards the synthesis of triacylglycerols which are the major lipid constituent of the LDs [3].…”
Section: Lipid Droplet Generation and Apoptosismentioning
confidence: 99%